تقيس األشعة فوق البنفسجية في كواشف األثر النووي العضوية UV-Visible مطيافية باستخدام CR-39 , CN- LR-115 85 - علي, فراس محمد; الجبوري, حسين علي; حميد, احمد خلف (Al-Nahrain Journal of Science, 2018)
Ultraviolet Radiation dosimetry at the rang 34.28x103 erg/ mm2 to 377x103 erg/ mm2 was determined for CR-39, CN-85, LR-115 nuclear track detectors by using UV-Visible spectrophotometer at wavelengths range (304-312 nm, 320-344nm, 382-392 nm) respectively. The value of optical absorption peaks for wave length range was increased with increasing of radiation dose, which was the same behavior for CR-39 and CN-85 detectors, where as the behavior of LR-115 detector was different by appearing of the reciprocal in the optical absorption peaks at radiation dose 171.4x102 erg/mm2. We determined the linear equations which are described the behavior of changes in the absorbance at specified wavelength ranges with UV–radiation doses for CR-39, CN-85 and LR-115 detectors.In addition we could use CR-39, CN-85 to determine UV–radiation dose from the dose range 34.28x103 erg/mm2 to 171.4x102 erg/mm2 and use LR-115 detector for the dose range 171.4 x x103 erg/mm2 to 377 x103 erg/mm2.